2008
DOI: 10.1186/ar2477
|View full text |Cite
|
Sign up to set email alerts
|

TH-17 cells in rheumatoid arthritis

Abstract: Introduction The aim of this study was to quantify the number of T-helper (TH)-17 cells present in rheumatoid arthritis (RA) synovial fluid (SF) and to determine the level of interleukin (IL)-17 cytokine in RA, osteoarthritis (OA) and normal synovial tissue, as well as to examine SF macrophages for the presence of IL-23, IL-27 and interferon (IFN)-γ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
131
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 27 publications
9
131
2
2
Order By: Relevance
“…The identification of this new subtype of th17 cell has prompted renewed interest in IL-17 biology. IL-17 plays an important role in inflammation, and is critical in host defense against infectious disease, allergy, and autoimmune diseases such as rheumatoid arthritis and inflammatory bowel diseases, which include crohn's disease and ulcerative colitis (8,9). Interestingly, Il-17 also has been reported to be up-regulated in Helicobacter pylori (Hp) infected gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of this new subtype of th17 cell has prompted renewed interest in IL-17 biology. IL-17 plays an important role in inflammation, and is critical in host defense against infectious disease, allergy, and autoimmune diseases such as rheumatoid arthritis and inflammatory bowel diseases, which include crohn's disease and ulcerative colitis (8,9). Interestingly, Il-17 also has been reported to be up-regulated in Helicobacter pylori (Hp) infected gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these cytokines have been implicated in autoimmune diseases, and production of each has been described in the synovial tissue and synovial fluid of patients with RA (20,21). The frequency and number of IL-4ϩ cells were not increased in the lymph nodes and paws of immunized mice, nor did they differ between wild-type and CXCR6 Ϫ/Ϫ mice ( Figures 3A-C).…”
mentioning
confidence: 97%
“…Several studies have demonstrated higher expression of IL-27 in RA synovial tissue and in RA synovial fluid macrophages as compared with controls (4,5). The levels of IL-27 messenger RNA are significantly higher in RA synovial fluid monocytes than in those from controls (4).…”
Section: Interleukin-27: a Master Regulator In Inflammation Ursula Fementioning
confidence: 97%
“…Initial studies examining IL-27 function demonstrated a role in promoting early stages of activation of naive CD4ϩ T and Th1 cell differentiation (1,3,4). IL-27 can synergize with IL-12 to promote production of interferon-␥ (IFN␥) by CD4ϩ, CD8ϩ, and NK T cells (2).…”
Section: Interleukin-27: a Master Regulator In Inflammation Ursula Fementioning
confidence: 99%
See 1 more Smart Citation